Pengaruh Brand Awareness, Brand Image Dan Brand Loyalty Terhadap Brand Equity Pada Pengguna Sepatu Nike Di Jakarta - Juliana Juliana (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of this study are: First, to explore the effect of brand awareness towards brand equity. Second, to explore the effect of brand image towards brand equity. Third, to explore brand loyalty towards brand equity. The method of data collection is convenience sampling. The samples of this research are collected from 165 respondent, who used Nike shoes in Jakarta. The technique of data analysis used in this study was multiple regression analysis via the Statistical Package for Social Sciences computer programme version 18. The result are: (1) brand awareness has a positive impact toward brand equity; (2) brand image has a positive impact towards brand equity; (3) brand loyalty is the main impact towards brand equity.